Factors Associated with Functional Dyspepsia in Junior College Students of the Faculty of Nursing, University of Riau - Vyona Aurelyn; Nurul Huda; Nurhannifah Rizky Tampubolon (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Functional dyspepsia is a collection of symptoms in the form of an uncomfortable feeling in the upper abdomen, pain, bloating, early fullness, frequent belching, nausea and vomiting. This study used a correlation descriptive research design with a cross sectional approach. The research sample was 147 respondents who were taken based on inclusion criteria using a total sampling technique. The analysis used univariate analysis to see the distribution of frequencies and bivariate using the Chi-Square test. The data collection tool used was the Perceived Stress Scale (PSS) questionnaire, eating habits, irritative diets, and functional dyspepsia which had been tested for validity and reliability. The results of this study indicate that most students experience functional dyspepsia. The results of this study indicate the factors associated with functional dyspepsia in college students, namely eating regularity (0.021). Meanwhile, factors that were not related to functional dyspepsia included stress level (p = 0.162), history of NSAID consumption (p = 0.112), and irritative diet (p = 0.380) There is a relationship between eating regularity and functional dyspepsia. The results of this study are expected so that students can manage their diet and maintain stomach health properly, so that the incidence of functional dyspepsia in students can decrease.